Molecular cloning and nucleotide sequence of the gene encoding the major peptidoglycan hydrolase of Lactococcus lactis, a muramidase needed for cell separation. - Buist, G (1995)
A gene of Lactococcus lactis subsp. cremoris MG1363 encoding a peptidoglycan hydrolase was identified in a genomic library of the strain in pUC19 by screening Escherichia coli transformants for cell wall lysis activity on a medium containing autoclaved, lyophilized Micrococcus lysodeikticus cells. In cell extracts of L. lactis MG1363 and several halo-producing E. coli transformants, lytic bands of similar sizes were identified by denaturing sodium dodecyl sulfate (SDS)-polyacrylamide gels containing L. lactis or M. lysodeikticus cell walls. Of these clearing bands, corresponding to the presence of lytic enzymes with sizes of 46 and 41 kDa, the 41-kDa band was also present in the supernatant of an L. lactis culture. Deletion analysis of one of the recombinant plasmids showed that the information specifying lytic activity was contained within a 2,428-bp EcoRV-Sau3A fragment. Sequencing of part of this fragment revealed a gene (acmA) that could encode a polypeptide of 437 amino acid residues. The calculated molecular mass of AcmA (46,564 Da) corresponded to that of one of the lytic activities detected. Presumably, the enzyme is synthesized as a precursor protein which is processed by cleavage after the Ala at position 57, thus producing a mature protein with a size of 40,264 Da, which would correspond to the size of the enzyme whose lytic activity was present in culture supernatants of L. lactis. The N-terminal region of the mature protein showed 60% identity with the N-terminal region of the mature muramidase-2 of Enterococcus hirae and the autolysin of Streptococcus faecalis. Like the latter two enzymes, AcmA contains C-terminal repeated regions. In AcmA, these three repeats are separated by nonhomologous intervening sequences highly enriched in serine, threonine, and asparagine. Genes specifying identical activities were detected in various strains of L. lactis subsp. lactis and L. lactis subsp. cremoris by the SDS-polyacrylamide gel electrophoresis detection assay and PCR experiments. By replacement recombination, an acmA deletion mutant which grew as long chains was constructed, indicating that AcmA is required for cell separation.